2010
DOI: 10.2174/092986710792065036
|View full text |Cite
|
Sign up to set email alerts
|

What is Known About the Antiviral Agents Active Against Bovine Viral Diarrhea Virus (BVDV)?

Abstract: Viruses belonging to the Flaviviridae family cause clinically significant diseases in humans and animals. This family includes three genera: Pestivirus [including bovine viral diarrhea virus (BVDV)], Flavivirus [including yellow fever virus (YFV), dengue virus, and West Nile virus (WNV)], and Hepacivirus [including hepatitis C virus (HCV)]. BVDV is responsible for major losses in cattle, causing a range of clinical manifestations, and is also a problematic contaminant in the laboratory. Noncytopathic BVDV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 81 publications
0
23
0
3
Order By: Relevance
“…Since then, TSCs displaying antineoplastic (12), antibacterial (13), antifungal (14), antiprotozoal (15) and antiviral (16) activity have been reported. Moglioni et al designed novel 1-indanone TSC candidate drugs that have shown in vitro activity against viruses, bacteria and fungi (17)(18)(19)(20). For example, 5,6-dimethoxy-1-indanone TSC (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, TSCs displaying antineoplastic (12), antibacterial (13), antifungal (14), antiprotozoal (15) and antiviral (16) activity have been reported. Moglioni et al designed novel 1-indanone TSC candidate drugs that have shown in vitro activity against viruses, bacteria and fungi (17)(18)(19)(20). For example, 5,6-dimethoxy-1-indanone TSC (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 5,6-dimethoxy-1-indanone TSC (Fig. 1a) displayed a 7-fold increase in the selectivity index against the virus of the bovine viral diarrhea (BVDV), a surrogate model of the hepatitis C virus (HCV), with respect to ribavirin (17,20); ribavirin is the first-choice anti-HCV agent combined with pegylated interferon-alpha. However, TSCs display extremely low aqueous solubility and precipitate rapidly in the culture medium, leading to unreliable antiviral half maximal inhibitory concentration (IC 50 ) data (17).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we reported on the synthesis and antiviral activity of a series of 1-indanone thiosemicarbazone derivatives as well as the effect of the substituents in the aromatic ring and of the thiosemicarbazone group on their activity (18,19). In the present study we characterized the antiviral activity of the most active derivative, TSC, which showed highly selective activity against BVDV by blocking the viral RNA synthesis in cell culture and in isolated BVDV RCs.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, we reported on the anti-BVDV activity exerted by the thiosemicarbazone derived from 5,6-dimethoxy-1-indanone (TSC) (18,19). Here, we describe a further characterization of the antiviral activity of TSC.…”
Section: Bovine Viral Diarrhea Virus (Bvdv)mentioning
confidence: 90%
“…The bovine viral diarrhea virus (BVDV), a member of the Flaviviridae family (genus Pestivirus ), shares similarities with HCV (genus Hepacivirus , Flaviviridae family) in terms of their replication cycles, biology and genetic organization, and shows the functionally homologous nature of many of their gene products, which are considered to be major targets for the development of anti-HCV agents [10]. …”
Section: Introductionmentioning
confidence: 99%